2017
DOI: 10.1371/journal.pone.0182791
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of selection as a cause for racial disparities in fibroproliferative disease

Abstract: Fibroproliferative diseases are common complex traits featuring scarring and overgrowth of connective tissue which vary widely in presentation because they affect many organ systems. Most fibroproliferative diseases are more prevalent in African-derived populations than in European populations, leading to pronounced health disparities. It is hypothesized that the increased prevalence of these diseases in African-derived populations is due to selection for pro-fibrotic alleles that are protective against helmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…The top variant in the WNT4/CDC42 had opposite directions of effect in African and European ancestry women, and associated variants in the TP53 locus were only polymorphic in European women. We have previously reported evidence for differential burdens of risk-increasing alleles for fibroproliferative traits across global populations that are consistent with prevalence disparities (Hellwege et al, 2017b). This finding was recently extended to evaluate only fibroid risk variants across populations, with an increased mean burden of risk alleles in black fibroid cases and controls from UKB compared to other racial/ethnic groups, with a similar result using frequencies from the gnomAD browser (Välimäki et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…The top variant in the WNT4/CDC42 had opposite directions of effect in African and European ancestry women, and associated variants in the TP53 locus were only polymorphic in European women. We have previously reported evidence for differential burdens of risk-increasing alleles for fibroproliferative traits across global populations that are consistent with prevalence disparities (Hellwege et al, 2017b). This finding was recently extended to evaluate only fibroid risk variants across populations, with an increased mean burden of risk alleles in black fibroid cases and controls from UKB compared to other racial/ethnic groups, with a similar result using frequencies from the gnomAD browser (Välimäki et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have shown that risk of broproliferative disease including keloids (Niessen et al, 1999), glaucoma (Morris et al, 1999, Racette et al, 2003, hypertension (Dustan, 1992, Suthanthiran et al, 2000, nephrosclerosis (August and Suthanthiran, 2003), scleroderma (Mayes et al, 2003), sarcoidosis (Rybicki et al, 1998), asthma (Barnes et al, 2007, Lester et al, 2001, Newth et al, 2012, Nickel et al, 1999, and broids (Flake et al, 2003), varies by race/ethnicity. Further supporting this are ndings from our group that demonstrated that the frequency of broproliferative risk alleles varies by geographic ancestry with a much higher burden among African-ancestry populations and lower among European-derived populations (Hellwege et al, 2017). Admixture mapping analysis of broid risk and multiple broid risk also demonstrates increased risk among Black women compared to White women (Bray et al, 2017, Giri et al, 2017.…”
Section: Introductionsupporting
confidence: 64%
“…However, there is large heterogeneity in symptomology, broid location, and broid growth, both within and between patients, demonstrating the complexity of mechanisms underlying the development and growth of broids (Ciavattini et al, 2013, Commandeur et al, 2015. We have published evidence that polygenic selection has occurred at risk loci for several broproliferative traits between African and non-African populations, which may contribute to racial disparities in risk and severity (Hellwege et al, 2017). In these studies we demonstrated that across published GWAS of broproliferative diseases there is strong evidence of increasing selection among those of African ancestry when compared to those of non-African ancestry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like CCCA, FPDs such as systemic sclerosis, keloids, atherosclerosis, and uterine fibroids (UFs) are all characterized by persistent low-grade inflammation and irritation that results in end-stage fibrosis. 7,8 The risk of certain FPDs is increased in people of African descent, and this increased risk is thought to be secondary to the protective effect that profibrotic alleles offer against helminths found in Sub-Saharan Africa. 8,9…”
Section: Introductionmentioning
confidence: 99%